2002
DOI: 10.1128/jcm.40.10.3782-3788.2002
|View full text |Cite
|
Sign up to set email alerts
|

Serodiagnosis of Tuberculosis: Comparison of Immunoglobulin A (IgA) Response to Sulfolipid I with IgG and IgM Responses to 2,3-Diacyltrehalose, 2,3,6-Triacyltrehalose, and Cord Factor Antigens

Abstract: Nonpeptidic antigens from the Mycobacterium tuberculosis cell wall are the focus of extensive studies to determine their potential role as protective antigens or serological markers of tuberculous disease. Regarding this latter role and using an enzyme-linked immunosorbent assay, we have made a comparative study of the immunoglobulin G (IgG), IgM, and IgA antibody responses to four trehalose-containing glycolipids purified from M. tuberculosis: diacyltrehaloses, triacyltrehaloses, cord factor, and sulfolipid I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 24 publications
3
39
0
2
Order By: Relevance
“…In sputum (71). Several lipid moieties have been purified and intensely studied for their serological potential for TB diagnosis (44). Four lipid antigens, all acylated trehaloses (107), were evaluated in smear-positive patients and included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In sputum (71). Several lipid moieties have been purified and intensely studied for their serological potential for TB diagnosis (44). Four lipid antigens, all acylated trehaloses (107), were evaluated in smear-positive patients and included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Julián et al conducted a comparative study of IgG, IgM, and IgA antibody responses to four trehalose-containing glycolipids, including cord factor, purified from Mycobacterium tuberculosis in the sera from 92 TB patients. They concluded that IgG antibody was more sensitive, IgA antibody was more specific, and IgM reactivity was negligible for all the glycolipid antigens used (10). Since TBGL is a glycolipid antigen containing cord factor, anti-TBGL IgA may yield a higher specificity than does anti-TBGL IgG, and the detection of both anti-TBGL IgG and anti-TBGL IgA may improve the diagnostic value.…”
Section: Discussionmentioning
confidence: 99%
“…As in other studies [10], the ROC curve was used to determine the best specificity values for the tests without a major loss in sensitivity and to identify the most accurate test (Figure 1). Julian et al (2002) showed that adult tuberculosis patients have a specific IgA response to glycolipid antigens. However, they found that tests detecting immunoglobulin A had lower sensitivity (66%) and greater specificity (88%) than IgG.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors can influence the reactivity of the test, such as the patient's immunological "status" and the stage and duration of the disease at the moment that the patient was included in the study [16][17][18]. When the ELISA tests using different antigens were carried out with sera from groups III and IV, there was less variation in specificity with the glycolipid antigen (88%-100%).…”
Section: Discussionmentioning
confidence: 99%